Tumoral pSMAD2 as a prognostic biomarker in early-stage breast cancer : insights from the randomized SweBCG91RT trial - Stenmark Tullberg, Axel; Thurfjell, Viktoria; Kovács, Anikó; Micke, Patrick; Moustakas, Aristidis; Killander, Fredrika; Niméus, Emma; Holmberg, Erik; Karlsson, Per; Strell, Carina (Breast Cancer Research and Treatment, 2025)
Background/Aim: The TGF-β pathway can influence breast cancer progression and therapy efficacy, exhibiting both pro- and anti-tumoral effects. This study examined the impact of active TGF-β signaling on recurrence and radiotherapy (RT) benefit in early-stage breast cancer, using nuclear phosphorylated Smad2 (pSMAD2) as a marker for pathway activation. Methods: Tissue-microarrays from 1178 stage I-IIA breast cancer patients in the SweBCG91RT trial (randomized to breast-conserving surgery with or without RT) were analyzed. pSMAD2 immunohistochemistry was scored as the mean percentage of tumor cells with nuclear staining. Recurrence risk and RT benefit were evaluated. Results: pSMAD2 scores were heavily skewed, with 45% of tumors demonstrating high staining (≥ 80% tumor cells), 38% medium (21–79%), and 17% low (≤ 20%). Low pSMAD2 tumors were associated with higher grade and larger size but not with subtype. Medium pSMAD2 tumors had a significantly increased ipsilateral breast tumor recurrence risk than high pSMAD2 tumors (HRadjusted = 1.82, p = 0.002), while no differences were observed for low pSMAD2 tumors. A similar result was obtained with all recurrences as endpoint. RT benefit was consistent across all pSMAD2 groups. In Luminal tumors, higher tumoral pSMAD2 levels were inversely correlated with tumor-infiltrating lymphocytes (TILs). Conclusion: Medium pSMAD2 levels were linked to an increased recurrence risk compared to high levels, suggesting a tumor-suppressive role of TGF-β in early breast tumorigenesis. However, no significant differences were noted for low pSMAD2 levels. In Luminal tumors, TGF-β signaling was negatively associated with TILs. These findings indicate that therapeutic targeting of TGF-β warrants careful consideration of tumor stage and subtype.
Publisher Copyright: © The Author(s) 2025.
Keywords: Breast cancer; Immune cells; Prognosis; Radiotherapy; SMAD2; TGF-β signaling